Empowerment of elementary school teachers in the HPV vaccination program in Subang Regency - Kurnia Eka Wijayanti; Lucky Angkawidjadja Roring; Imas Damayanti; Euis Heryati; Nur Faizah Romadona (Jurnal Abmas, 2025)
Cervical cancer is most common among women in Indonesia, with the main causes being Human Papillomavirus (HPV) types 16 and 18. Vaccination is an effective strategy for reducing the incidence of cervical cancer. Since 2023, the Indonesian government has provided free HPV vaccines for girls in grades 5 and 6 of elementary school. In its implementation, teachers play a role in shaping students' perceptions of the importance of reproductive health, which needs to be communicated to parents. This community service activity aims to increase teachers' knowledge about the HPV vaccine and cervical cancer, as well as strengthen their skills in communicating the importance of HPV vaccination to parents. The intervention was carried out through interactive discussion sessions, supported by educational materials in the form of banners and guidebooks that teachers could use when conducting outreach to parents. A total of 50 teachers in Subang Regency participated in this activity. Qualitative evaluation showed that most reported an increase in knowledge and felt more confident in discussing HPV vaccines with parents. These findings suggest that health promotion programs targeting teachers can effectively support school-based HPV vaccination initiatives.   Abstrak Kanker serviks paling sering terjadi pada perempuan di Indonesia dengan penyebab utama dari Human Papillomavirus (HPV) tipe 16 dan 18. Vaksinasi sebagai strategi efektif untuk menurunkan insidensi kanker serviks, sejak tahun 2023 pemerintah Indonesia menyediakan vaksin HPV secara gratis bagi anak perempuan kelas 5 dan 6 sekolah dasar. Dalam pelaksanaannya, guru berperan untuk membentuk persepsi murid akan pentingnya kesehatan reproduksi, hal tersebut perlu dikomunikasikan dengan orang tua. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan pengetahuan guru mengenai vaksin HPV dan kanker serviks, serta memperkuat keterampilan mereka dalam mengkomunikasikan pentingnya vaksinasi HPV kepada orang tua. Intervensi dilakukan melalui penyuluhan dengan diskusi interaktif, didukung materi edukasi berupa banner dan buku panduan yang dapat digunakan guru ketika melakukan sosialisasi kepada orang tua. Sebanyak 50 guru di Kabupaten Subang berpartisipasi pada kegiatan ini. Evaluasi kualitatif menunjukkan bahwa sebagian besar melaporkan peningkatan pengetahuan serta merasa lebih percaya diri untuk berdiskusi dengan orang tua mengenai vaksin HPV. Temuan ini menunjukkan bahwa program promosi kesehatan yang berfokus pada guru dapat mendukung  program vaksinasi HPV berbasis sekolah. Kata Kunci: kampanye kesehatan; kanker serviks; vaksin HPV